2008
DOI: 10.1007/s00467-008-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of dexamethasone on decreasing urinary cytokines in children with acute pyelonephritis

Abstract: Cytokines play a major role in renal scar formation following febrile urinary tract infection (UTI). We investigated the role of dexamethasone combined with antibiotics in diminishing urinary interleukin-6 (UIL-6) and UIL-8 concentrations during the acute phase of pyelonephritis compared with standard antibiotic therapy. UIL-6 and UIL-8 concentrations were determined by enzyme immunoassay in 34 children with pyelonephritis who were treated with ceftriaxone plus dexamethasone (case group) and in 20 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…They are involved in B cell and T cell proliferation and neutrophil chemoattraction, along with secretion of CRP, immunoglobulins, and acute-phase proteins (2,6,8,10) Clinical manifestations of APN depend on the production of different cytokines, and measurement of urinary ILs seems to be useful for the rapid diagnosis and localization of inflammation within the urinary tract system. Increased urinary IL-1, IL-4, IL-6, and IL-8 concentrations have been reported in children with acute febrile UTIs compared to the healthy children and those with lower UTIs, asymptomatic bacteriuria, and non-renal febrile infections (2,(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in B cell and T cell proliferation and neutrophil chemoattraction, along with secretion of CRP, immunoglobulins, and acute-phase proteins (2,6,8,10) Clinical manifestations of APN depend on the production of different cytokines, and measurement of urinary ILs seems to be useful for the rapid diagnosis and localization of inflammation within the urinary tract system. Increased urinary IL-1, IL-4, IL-6, and IL-8 concentrations have been reported in children with acute febrile UTIs compared to the healthy children and those with lower UTIs, asymptomatic bacteriuria, and non-renal febrile infections (2,(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…If not diagnosed early and left untreated timely, UTIs can lead to scar formation, hypertension and end stage renal disease (ESRD) (1-7). There have been many efforts to study mediators of inflammation trying to halt deleterious effects of UTI such as scar formation (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a study by Sharifian et al, it was concluded that the administration of dexamethasone could possibly prevent the formation of kidney scar [21]. Regarding this and comparing the side effects of dexamethasone and vitamin A, again the beneficial effects of vitamin A make this chemical as a valuable drug in treatment of acute pyelonephritis and eventually in prevention of kidney scar formation.…”
Section: Discussionmentioning
confidence: 92%
“…The majority of these studies used laboratory animal models [3,9,14,18,20], and to our knowledge, only two studies of this kind were performed on children [13,21]. There are other studies in which the effects of pentoxifylline, melatonin, and ebselen on prevention of renal scar were examined, but again all were carried out on animal models [10,11,26].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation